DAMPAK HASRAT TERHADAP KARAKTER DALAM NOVELA THE LITTLE PRINCE KARYA ANTOINE DE SAINT-EXUPERY - YOBEL, LEONARD (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACTThis research entitled â€œThe Impact of Desire to the Characters in the Novella The Little Prince by Antoine de Saint-Exuperyâ€ is written to fullfil the requirement of accomplishing bachelorâ€™s degree in English Department Faculty of Humanities Sam Ratulangi university. The focus of this research is identifying and analyzing the desire and the impact of desire to the charactersâ€™ psychology.In this research, desireâ€™s theory by Steven Reiss (2000) was used to analyze the desires that give impact to the characters. The methodology used in the research was divided into three steps: preparation, data collection, and data analysis. In preparation, the writer read the novella and other literatures related to the topic. In data collection, through the characterâ€™s dialogue, plot and action the writer found the desires and their impacts. In data analysis, the writer used the intrinsic approach and the extrinsic approach to find the impact of desire to the charactersâ€™ psychology by paying attention to the dialogues, plot and actions.The results of this research show that desire does impact the charactersâ€™ psychology to get what they want. There are sixteen basic desires proposed by Reiss (2000) but the writer only found ten desires in the novella which are power, curiosity, acceptance, order, saving, social contact, status, vengeance, romance, and tranquility. Â Keywords: The Little Prince, Antoine de Saint-Exupery, Desire, Intrinsic and Extrinsic Approaches